The Correlation among English Learning Anxiety, Speaking and Writing Achievements of Senior High School Students - Dian Eva Lestari; Bambang Loeneto; Diemroh Ihsan (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2019)
The objectives of the study were to analyze whether or not there were a significant correlation among English learning anxiety, speaking, and writing achievements of the eleventh graders’. The sample of the study were 112 eleventh graders’. They were selected randomly. The study used quantitative research design. The questionnaire and the writing and speaking tests were done to analyze the data. The researcher used foreign language classroom anxiety scale questionnaire to measure the students’ English learning anxiety with five-point likert scale, and speaking and writing tests were used to measure the students’ speaking and writing achievements. Pearson product moment correlation and regression were analyzed by using SPSS. The results of study were negative low correlation between English learning anxiety and speaking achievement (r=-.269 with p<0.01) and English learning anxiety and writing achievement (r=-.213 with p<0.05).